Adjuvant therapies in venous leg ulcer management: A scoping review. Issue 5 (20th May 2019) - Team, Victoria; Chandler, Peter G.; Weller, Carolina D.
Abstract: Compression therapy is the current evidence‐based approach to manage venous leg ulcers (VLU); however, adherence is a major barrier to successful treatment. Combination approaches may relieve the burden of treatment by shortening the time to ulcer healing. This scoping review conducted by Australian researchers aimed to establish the evidence of effectiveness of various adjuvant methods on wound healing and recurrence. Randomized Controlled Trials (RCTs), and Systematic Reviews (SR) and Meta‐Analyses (MA) on VLU management approaches published from January 2015 to December 2018 were included in this review. The articles included in the scoping review were grouped according to the management approaches, including (1) pharmaceutical interventions, (2) surgical interventions, (3) topical agents, (4) the use of devices, and (5) other, such as physiotherapy and psychological interventions. Results of this scoping review indicate that there is a limited high‐quality evidence of effectiveness in most adjuvant therapies on wound healing and recurrence. Given the low‐quality evidence observed in this scoping review for adjuvant treatments, the implication for practice is that current management guidelines be followed. Further rigorous studies have the potential to produce better quality evidence. Quality of evidence can be improved by ensuring large sample sizes of a single etiology wounds, standardizing reporting outcomes, and maintaining detailed and evidence‐based protocols in physiological or psychological interventions.